INTERNALIZATION OF THE VALUES OF RELIGIOUS MODERATION IN THE MILLENNIAL GENERATION BASED ON ISLAMIC EDUCATION (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2025)
The internalization of religious moderation values is essential in shaping a tolerant, inclusive, and morally upright millennial generation. In the face of globalization, characterized by rapid information exchange and cultural diversity, Islamic education plays a strategic role in instilling principles of balance (tawassuth), tolerance (tasamuh), and justice (‘adalah). Through adaptive and integrative pedagogical approaches, these values can be effectively embedded in the lives of young people. This study aims to examine the process of internalizing religious moderation through Islamic education and its impact on the religious attitudes of the millennial generation. A qualitative descriptive approach based on literature review is used in this research. The findings reveal that contextual, participatory, and character-oriented Islamic education serves as a key medium in reinforcing the values of religious moderation among millennials.